TECHNICAL AND OPERATIONAL MEASURES TO REDUCE GREENHOUSE GAS EMISSIONS AND IMPROVE THE ENVIRONMENTAL AND ENERGY EFFICIENCY OF SHIPS - Oleg ONISHCHENKO; Volodymyr GOLIKOV; Oleksiy MELNYK; Svitlana ONYSHCHENKO; Kostiantyn OBERTIUR (Scientific Journal of Silesian University of Technology. Series Transport, 2022)
Every year, the dynamics of implementation of projects aimed at improving the efficiency of energy use is gradually increasing at different levels and in different industries. It has spread in the areas of design, modernization and reconstruction of energy-efficient buildings and structures, design and construction of elements of industrial infrastructure, and technological production processes. Introduction of such projects is a priority for enterprises and companies of various types of economic activity. Thus, the leading industries develop strategies to improve environmental safety and energy efficiency - shipping is no exception, where the process of improving energy efficiency is carried out through various mechanisms, ultimately leading to a reduction in emissions of pollutants, but having a negative impact on the performance of the commercial operation of the ship. Problems of ensuring energy efficiency along with increasing requirements for environmental safety of transport and strengthening the responsibility of shipowners become the focus of research of modern theory and practice of operation of means of maritime transport. The issues of improvement of universal principles of energy efficiency within individual shipping companies and development of tools for economic analysis of energy efficiency of own fleet, search for new ways of forming professional competencies of ship crew members in the field of energy efficiency continue to be topical as well.